Molecular epidemiology and mechanisms of colistin and carbapenem resistance in Enterobacteriaceae from clinical isolates, the environment and porcine samples in Pretoria, South Africa - Mbelle, Nontombi (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 2020.